Transient Patellar Dislocation Resulting in Simultaneous Osteochondral Fractures of Patella and Lateral Femoral Condyle – A Case Report - Jalan, Divesh (J Clin Diagn Res, 2014)
Transient Patellar dislocations are commonly associated with bony contusions or osteochondral fractures involving the medial facet of patella or lateral femoral condyle. Simultaneous osteochondral fractures are rare and have not been reported in the adult. The authors report a case of combined osteochondral fracture of patella and lateral femoral condyle following acute patellar dislocation in an adult, which was misdiagnosed as meniscal injury. Both the osteochondral fracture fragments were rigidly fixed with headless compression screws and repair of the medial retinaculum was done. At latest follow up after two years, patient had regained full range of motion with no further episodes of patellar dislocation. The rarity of this combination of injury along with difficulty in interpreting radiographs makes this case interesting.